Multi-agent Intelligent Ensembles with Professional Competencies, Pattern Recognition and Decision Making - Evgeny Bryndin (Britain International of Exact Sciences (BIoEx) Journal, 2022)
Each competence is exercised by an intellectual agent with a competent functional professional image. Intellectual agents form an ensemble with clever ethical artificial intelligence. The use of an ensemble with intelligent ethical artificial intelligence in various environments is carried out by synergistically adjusting the interaction of intelligent agents based on data from a specific environment obtained by an analytical competent intellectual agent. Modeling holographic processes of the human psyche based on artificial intelligence of machine learning with Fourier transformation using full parametric sequences of necessary and sufficient data of holograms of target objects solves the problem of their unambiguous detection in different environments and in different conditions. An ensemble of intelligent decision-making agents is a cognitive information system that makes a decision based on an objective analysis of available data in difficult situations, in an interactive mode, taking into account performance criteria and resource-time constraints. Decision-making criteria are functionalities that express preferences and allow ranking the quality of decisions. Decisions are made on the basis of rules. Decision rules are a set of logical constructs used to produce a decision based on criteria, data, and knowledge. An ensemble of intellectual agents with professional competencies, pattern recognition and decision-making fully model the abilities of the human psyche.